To expand the expression \(-\frac{7}{6}(3g + 2)\), we'll distribute \(-\frac{7}{6}\) to both terms inside the parentheses:
-
Multiply \(-\frac{7}{6}\) by \(3g\): \[ -\frac{7}{6} \cdot 3g = -\frac{7 \cdot 3}{6}g = -\frac{21}{6}g = -\frac{7}{2}g \]
-
Multiply \(-\frac{7}{6}\) by \(2\): \[ -\frac{7}{6} \cdot 2 = -\frac{14}{6} = -\frac{7}{3} \]
Now, combine the results: \[ -\frac{7}{2}g - \frac{7}{3} \]
So, the expanded expression is: \[ -\frac{7}{2}g - \frac{7}{3} \]
Thus, the correct response is: −7/2g−7/3